2019
DOI: 10.3390/rs11141727
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Building Outline Extraction from ALS Point Clouds by Ordered Points Aided Hough Transform

Abstract: Many urban applications require building polygons as input. However, manual extraction from point cloud data is time- and labor-intensive. Hough transform is a well-known procedure to extract line features. Unfortunately, current Hough-based approaches lack flexibility to effectively extract outlines from arbitrary buildings. We found that available point order information is actually never used. Using ordered building edge points allows us to present a novel ordered points–aided Hough Transform (OHT) for extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Second, in the building modelling algorithm, the filtering operation is applied to the building point cloud before starting the construction of the building model. Hence, the filtering algorithm aims to eliminate the undesirable points before starting the modelling step [34][35][36]. In the two last cases, the filtering algorithm is merged with the classification or modelling approaches.…”
Section: Accuracy Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, in the building modelling algorithm, the filtering operation is applied to the building point cloud before starting the construction of the building model. Hence, the filtering algorithm aims to eliminate the undesirable points before starting the modelling step [34][35][36]. In the two last cases, the filtering algorithm is merged with the classification or modelling approaches.…”
Section: Accuracy Comparisonmentioning
confidence: 99%
“…Despite this, the influence of the employed filtering operation will appear in the quality of the final product (building mask or building model). This is why the accuracy of the suggested approach is compared with the accuracy of the approaches [7,9,11,[34][35][36] in the context of comparing the efficacity of the suggested approach with other similar approaches suggested in the literature To clarify how this comparison can be achieved, let us take this example. First, the result of an urban point cloud classification is a building mask named m 1 .…”
Section: Accuracy Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Many algorithms have been developed for building class classification from LiDAR point clouds, for instance using input attributes from DSM and ortho image [11], a supervised parametric classification algorithm [12], the theory of Dempster-Shafer for two different stages of classification process [13], the geometry and echo information of LiDAR point cloud to estimate parameters for the learning model [14], and a multiple-entity based classification method [15]. Regarding building extraction, a lot of research found alternative methods for building extraction from LiDAR, for example using OBIA (Object Based Image Analysis) with the use of class modelling methods [16], data fusion of point and grid-based features using a graph cuts algorithm [17], a novel ordered points-aided Hough Transform (OHT) [18], a modified LEGION segmentation [19], automatic process with emphasis on top-down approaches [20], and rule-based segmentation of non-ground LiDAR point clouds [21].…”
Section: The Development Of Lidar Creates a New Approach For Automatimentioning
confidence: 99%
“…Various algorithms have been further applied for building outline extraction from point clouds, e.g. random sample consensus (RANSAC) (Jarzabek-Rychard, 2012), Hough transform (Widyaningrum et al, 2019), convex hull (Sampath and Shan, 2007), alpha shape (dos Santos et al, 2019) or combinations of them (Albers et al, 2016). A comprehensive review of the methods for building outline extraction from ALS point clouds has been provided by Tomljenović et al (2015).…”
Section: Introductionmentioning
confidence: 99%